Mango Endophyte and Epiphyte Microbiome Composition during Fruit Development and Post-Harvest Stages - Malick Bill (MDPI AG, 2021)
The influence of the development stage and post-harvest handling on the microbial composition of mango fruit plays a central role in fruit health. Hence, the composition of fungal and bacterial microbiota on the anthoplane, fructoplane, stems and stem-end pulp of mango during fruit development and post-harvest handling were determined using next-generation sequencing of the internal transcribed spacer and 16S rRNA regions. At full bloom, the inflorescence had the richest fungal and bacterial communities. The young developing fruit exhibited lower fungal richness and diversities in comparison to the intermediate and fully developed fruit stages on the fructoplane. At the post-harvest stage, lower fungal and bacterial diversities were observed following prochloraz treatment both on the fructoplane and stem-end pulp. Ascomycota (52.8%) and Basidiomycota (43.2%) were the most dominant fungal phyla, while Penicillium, Botryosphaeria, Alternaria and Mucor were detected as the known post-harvest decay-causing fungal genera. The Cyanobacteria (35.6%), Firmicutes (26.1%) and Proteobacteria (23.1%) were the most dominant bacterial phyla. Changes in the presence of Bacillus subtilis following post-harvest interventions such as prochloraz suggested a non-target effect of the fungicide. The present study, therefore, provides the primary baseline data on mango fungal and bacterial diversity and composition, which can be foundational in the development of effective disease (stem-end rot) management strategies.